Culture, Selection, and International Migration - Laura Renner; Tim Krieger; Jens Ruhose (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper looks at the e ffect of cultural barriers on the skill selection of international migration. The data covers bilateral migration stocks by skill level in 2000 from about 99 sending countries to the main 15 destination countries. We use genetic distance as a proxy for cultural distance and exploit exogenous variation in genetic distance in 1500 to show that a higher genetic distance leads to a higher selectivity of migrants. This reveals that cultural traits are an important determinant of the skill mix of current migrant populations.
Keywords: F22; J61; Z10; 330